Thai Students Enthusiasm in Learning Indonesian at UIN Sayyid Ali Rahmatullah Tulungagung - Malinee Masmummat; Wisaruta Butsaman; Oktavia Winda Lestari; Nabila Fatin (CV. Institute of Multidisciplinary Research and Community Service (CV. IMRECS)), 2024)
Abstract: Indonesian was originally Malay which was agreed at the 1928 youth congress as a unified language for the Indonesian nation. The presence of foreign students, especially Thais, is an attraction for researchers to conduct research on Thai students' enthusiasm for learning Indonesian. This research aims to find out how enthusiastic Thai students are in learning Indonesian. The research method used in this research is a qualitative descriptive method with data sources obtained through observation and interviews. The results of this research are, 1) Immersion Program in BIPA Learning at UIN Sayyid Ali Rahmatullah Tulungagung, 2) Learning BIPA by Role Playing, 3) Folklore (Floklore) in BIPA Learning at UIN Sayyid Ali Rahmatullah Tulungagung, and 4) Student Communication Accommodation Thailand at UIN Sayyid Ali Rahmatullah Tulungagung. Keywords: enthusiasm, learning Indonesian, BIPA, Thailand.